¿Es la Lectura un Componente Importante de la Cultura Organizacional en las Empresas? (2019)
Reading through language is an activity that consists of interpreting and deciphering, through sight, the phonic value of a series of written signs, either mentally (silently) or loudly (orally). This activity is characterized by the translation of symbols or words and phrases. Reading is to make possible the interpretation and understanding of written materials, evaluate them and use them for our needs. The reading of texts is the main source of personal enrichment, because it allows us to acquire knowledge, improve our communication skills, develop our analysis capacity; It also helps us think clearly or solve problems. It is convenient that before reading it is convenient to know what the purpose of reading is, that is, why we are interested in reading. When we know that we are looking for a reading, we are better prepared to get the materials that can satisfy our interests. The objective of this work is to know if reading becomes an important component in organizations, taking into account that this activity allows us to know, understand and interpret the environment, and then acquire, develop and encourage cultural values, ranging from ethical values, morals, responsibility, commitment, etc., which can impact, contribute to forge our own culture.